The shape of things : Male body image amongst South African University Students - Picton, Jonathan Peter (My University, 2008)
This research explored trends in male body image amongst South African men aged 18 to 25 years. A questionnaire consisting of a demographic section, the Body Image Test, the Behaviours Checklist and the Eating Disorders Inventory was administered to 50 male students from the University of the Witwatersrand. Trends in body dissatisfaction, body enhancing behaviour and eating disorder symptoms were examined. Correlation analyses were used to infer relationships between these three variables. The results showed that the sample group on average view themselves as overly muscular and have a body image ideal that is less muscular than their perceived body image. This trend is contrary to trends reported in international studies and is thought to represent the cultural effects of using a South African population that is diverse in its composition as compared to an American or European samples that are more homogenous in nature. The results also showed that there were differences in body image trends between different racial groupings, although the results did indicate that across the racial groupings there was a similar societal body image ideal that represents a global trend towards a lean, muscular male body image. The results showed that the sample did not engage in body enhancing behaviours that are considered excessive or indicative of body image dissatisfaction. This was also reflected by the results on the Eating Disorders Inventory that showed considerably lower scores on the symptom scales when compared to a clinical eating disordered population and a non-clinical female comparison group. The results also showed that the sample had lower scores on the behavioural symptom scales yet higher scores on the attitudinal symptom scales. This indicates that the sample did not display any significant eating disorder behaviours yet did display personality traits that are correlated to eating disordered behaviour. There was no correlation between body dissatisfaction and body enhancing behaviour. There was a positive correlation between body dissatisfaction and the symptom scale of interpersonal distrust. A positive correlation also occurred between body enhancing behaviour and the symptom scales for perfection and drive for thinness. Limitations of the study and recommendations for future research are discussed.
Keywords: male students; University of the Witwatersrand; male body image; body enhancing behaviours; body dissatisfaction